2023
DOI: 10.4103/jisp.jisp_509_21
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of subgingival irrigation and powered toothbrush as home care maintenance protocol in type 2 diabetic patients with active periodontal disease: A 4-month randomized controlled trial

Jaspreet Kaur,
Vishakha Grover,
Jyoti Gupta
et al.

Abstract: Background: There is a bidirectional link between diabetes and periodontal disease. Control of active periodontal infection is an essential requisite to maintain optimal oral and systemic health in diabetic patients. The purpose of this study was to evaluate the efficacy of subgingival irrigation and powered toothbrush as home care maintenance protocol in type 2 diabetic patients with active periodontal disease compared to routine oral hygiene. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Twelve studies on oral irrigation's influence on markers of inflammation showed positive results. Water irrigation did not increase inflammation in vitro (Matthes et al 2023 ), or reduce gingival crevicular fluid (GCF) and salivary markers in gingivitis and periodontitis in two trials (Kaur et al 2023 ; Ramseier et al 2021 ). However, adjunctive water irrigation decreased GCF cytokines versus routine home care (Cutler et al 2000 ); adjunctive interdental brushing (Moore et al 2023 ); was more effective in participants with peri‐implant mucositis (Tütüncüoğlu et al 2022 ); and reduced blood markers in periodontitis and diabetes patients (Al‐Mubarak et al 2002 ; Cutler et al 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies on oral irrigation's influence on markers of inflammation showed positive results. Water irrigation did not increase inflammation in vitro (Matthes et al 2023 ), or reduce gingival crevicular fluid (GCF) and salivary markers in gingivitis and periodontitis in two trials (Kaur et al 2023 ; Ramseier et al 2021 ). However, adjunctive water irrigation decreased GCF cytokines versus routine home care (Cutler et al 2000 ); adjunctive interdental brushing (Moore et al 2023 ); was more effective in participants with peri‐implant mucositis (Tütüncüoğlu et al 2022 ); and reduced blood markers in periodontitis and diabetes patients (Al‐Mubarak et al 2002 ; Cutler et al 2000 ).…”
Section: Resultsmentioning
confidence: 99%